2010
DOI: 10.1097/aln.0b013e3181f90ccc
|View full text |Cite
|
Sign up to set email alerts
|

Slowing of the Hippocampal θ Rhythm Correlates with Anesthetic-induced Amnesia

Abstract: Background-Temporary, antegrade amnesia is one of the core desirable endpoints of general anesthesia. Multiple lines of evidence support a role for the hippocampal θ-rhythm, a synchronized rhythmic oscillation of field potentials at 4-12 Hz, in memory formation. Previous studies have revealed a disruption of the θ-rhythm at surgical levels of anesthesia. We hypothesized that modulation of θ-rhythm would also occur at subhypnotic but amnestic concentrations. Therefore we examined the effect of three inhaled age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 60 publications
2
41
1
1
Order By: Relevance
“…Whereas we observed increased hippocampal delta oscillations, hippocampal delta activities have been observed so far only in primates and humans but not rodents (64,65). Previous studies in rodents showed that theta-like oscillations in the hippocampus shifted to lower frequencies (i.e., delta range) during light anesthesia (∼1.0% isoflurane) (66,67). This finding suggests that our increased delta oscillation results might arise from increased theta-like oscillations after low-frequency stimulation.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Whereas we observed increased hippocampal delta oscillations, hippocampal delta activities have been observed so far only in primates and humans but not rodents (64,65). Previous studies in rodents showed that theta-like oscillations in the hippocampus shifted to lower frequencies (i.e., delta range) during light anesthesia (∼1.0% isoflurane) (66,67). This finding suggests that our increased delta oscillation results might arise from increased theta-like oscillations after low-frequency stimulation.…”
Section: Discussioncontrasting
confidence: 49%
“…Hippocampal-cortical activity is state dependent, so the light anesthesia used here may alter their characteristics (34,66,67,79). Nevertheless, prior work revealed synchronized interhemispheric delta oscillations as a major contributor to infraslow rsfMRI connectivity in anesthetized rodents (16,17).…”
Section: Discussionmentioning
confidence: 96%
“…Structures of the medial temporal lobe such as the hippocampus or amygdala that may undergo atrophy in patients with dementia 19 are also involved in anesthetic-mediated amnesia. 20,21 It is unclear from BIS values alone whether such cognitive processes are more vulnerable to the effects of general anesthetics in dementia patients.…”
Section: Neural Processes Involved In Cognition or Memory Were Not Mementioning
confidence: 99%
“…Les structures internes du lobe temporal, comme l'hippocampe ou l'amygdale susceptibles d'atrophie chez les patients atteints de démence 19 sont également impliquées dans l'amnésie induite par les anesthésiques. 20,21 On ne peut pas affirmer à partir des seules valeurs BIS si ces processus cognitifs sont plus vulnérables aux effets des anesthésiques généraux chez les patients atteints de démence.…”
Section: L'indice Bispectral Est Un Indice Limité De La Fonction Céréunclassified
“…An alternative that has been employed during trauma surgery is the antimuscarinic, anticholinergic drug scopolamine. In general, these pharmacologic routes to amnesia result in the inhibition of antegrade memory formation -that is, memories formed after the drug has been administered [9]. In other words, a suspected event of consciousness of surgical events cannot be 'erased' after the experience.…”
Section: If You Cannot Ensure Unconsciousness Then Prevent Memorymentioning
confidence: 99%